2017
DOI: 10.1002/cbin.10868
|View full text |Cite
|
Sign up to set email alerts
|

Induction of autophagy by an oleanolic acid derivative, SZC017, promotes ROS‐dependent apoptosis through Akt and JAK2/STAT3 signaling pathway in human lung cancer cells

Abstract: The signal transducers and activators of transcription 3 (STAT3) signaling pathway is a common feature in many solid tumors including non-small cell lung cancer, whereas current therapies usually fail to treat this disease in majority of cases. In the present study, we aimed to investigate the cytotoxic effect and the underlying mechanisms of SZC017, an oleanolic acid derivative, on human lung cancer cells. Cell viability was significantly decreased in SZC017-treated lung cancer cells. Mechanistically, SZC017 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Our RNA-Seq analysis identified multiple genes related to sanshool treatment and UVB irradiation in which the most remarkable results referred to CSF2 and the AKT-JAK2-STAT3 pathway. The JAK2-STAT3 signaling pathway, a core component of organ protection, is involved in various organs 25 . In the current study, sanshool exerted positive effects on the expression and secretion of CSF2 in UVB-irradiated HDFs.…”
Section: Discussionmentioning
confidence: 99%
“…Our RNA-Seq analysis identified multiple genes related to sanshool treatment and UVB irradiation in which the most remarkable results referred to CSF2 and the AKT-JAK2-STAT3 pathway. The JAK2-STAT3 signaling pathway, a core component of organ protection, is involved in various organs 25 . In the current study, sanshool exerted positive effects on the expression and secretion of CSF2 in UVB-irradiated HDFs.…”
Section: Discussionmentioning
confidence: 99%
“…STAT3, a member of the STAT family, may be activated by phosphorylation at the tyrosine residue 705 to regulate the release of growth factors and cytokines in gastric cancer (41). The activation of the JAK2/STAT3 signaling pathway was associated with the growth, migration and metastasis of lung cancer cells (42). Lei et al (43) revealed that the activation of the JAK2/STAT3 signaling pathway may promote the proliferation and migration of cancer cells as well as inhibit apoptosis in renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Upon phosphorylated by JAK2 at Try705, STAT3 undergoes dimerization and then translocates to the nucleus, where it binds with the promoter regions of target genes to promote their expression (Kurdi and Booz, ). It has been documented that STAT3 extensively participates in the regulation of numerous genes controlling cell survival, metabolism, inflammation, oxidative stress, and angiogenesis (Song et al, ; Wang et al, ). Moreover, STAT3 plays an important role in the hypertrophic growth of cardiomyocytes (Willey et al, ).…”
Section: Discussionmentioning
confidence: 99%